The perils of polling. - Cherry, S. (IEEE spectrum)
It's unusual and more than a bit surprising that in the short term, technologists want to slow down the move to electronic systems while many election officials are ready to speed ahead. If the officials started down the electronic voting path by underestimating the problems of deploying the technology, computer scientists may have underestimated the long-standing difficulties of conducting traditional all-paper elections. Election officials now seem to be coming to understand the merits and demerits of electronic voting systems. Overall, the current: debate over electronic voting has certainly raised the bar for election equipment. And every year, we get a chance to do better.